Structure of the House and Courtyard in Friuli Proposal for a Glossary - GUBIANI, RINO; SIGURA, MAURIZIA (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2021)
Houses (and courtyards, as houses in Friuli were rarely built in isolation, being usually part of a group of buildings used partly as dwellings and partly for rural purposes) have always been important in Friulian culture. In the building sector, a series of trades (bricklayers, carpenters, joiners, etc.) and a very precise and detailed terminology on structures, materials and so on, were established in Friuli. The study presented in this contribution aims to give an initial answer to the question: do houses, courtyards and rural buildings in Friuli have their own ethnically specific identity and precise terminological Friulian language glossary, or are they affected by other factors unrelated to ethnic specificity and the Friulian language?